Paint Shop Pro 9 for photographers - McMahon, Ken (Focal Press, 2005)
Ken McMahon and Robin Nichols have created a complete and easy-to-follow introduction to Jasc's Paint Shop Pro 9, allowing you to take full advantage of this popular photo-editor and graphics program in ways you would never have imagined. If you are an amateur digital photographer, web or graphic designer this book will provide you with everything you need to get the very best out of your images and achieve professional-looking results with this affordable but powerful consumer software. Paint Shop Pro 9 for Photographers offers an extensive variety of real life examples with clear, step-by-st.